Effects of Reproductive and Contractile Potential of “Makann” a Bi-herbal Formulation in Mice - Itemire, Anne Oghenekevwe; Idu, MacDonald; Enitome, Bafor Evi; Gabriel, Benjamin Ogunma (Darul Yasin Al Sys, 2025)
Spontaneous uterine contractions are strictly controlled and coordinated for the success of various reproductive functions. The aim of this study was to evaluate uterine activity of bi-herbal formulation of G. kola and C. papaya roots in rodents. Ex-vivo BH cumulative concentrations response on spontaneous contractions, oxytocin induced contraction in the presence and absence of calcium and potassium induced contraction were determined. In vivo reproductive investigation in female mice and oestrogenicity in immature rats were carried out using standard methods. In uterine contractility studies, there was an increase in amplitude of spontaneous contractions with a steady decrease in the frequency. An increase in oxytocin amplitude and frequency was observed in calcium physiological salt solution (PSS) however, only amplitude was increased in oxytocin calcium-free PSS. Potassium chloride had a slight increase in amplitude. The reproductive cycle and uterothrophic assay exhibited no significant increase in relative uterine weight. The histology of the ovary, cervix and uterus showed normal cellular structural architecture. Oestrous cycle regularity and cycle number were increased in the BH treatment groups. In conclusion, an increase in female hormone as evident in oestrous cycle response validate the use of this formulation in traditional medicine for the treatment of abnormal uterine bleeding.